The impact of the Islamic finance sector and Covid-19 pandemic on Indonesian economic growth period 2004Q1-2021Q3 - Cahyaningrum, Safira Aulia; Wibowo, Muhammad Ghafur (Journal of Islamic Economics Management and Business (JIEMB), 2022)
The Asian financial crisis in 1997 left the national banking system in disarray and liquidity problems. After that, following the Covid-19 pandemic which has increasingly complicated global economic sectors, such as tourism, trade and finance. In the financial sector, uncertainty has depressed the performance of global financial markets and caused the stock market to decline. A stock market is a place for transactions in financial instruments such as securities or stocks. This study aims to analyze the impact of the Islamic finance sector and the Covid-19 pandemic on the Indonesian economic growth period 2004Q1 – 2021Q3. Themethod used in this study is a quantitative method employing Autoregressive Distributed Lag (ARDL) analysis. This study demonstrates that Islamic finance has the potential to boost the economy. This study confirms the assumption that the financial sector affects economic growth (finance led growth). This research can be used as reference material in determining and making policies regarding the development of the Islamic finance sector in Indonesia, such as formulating strategies to encourage economic growth through Islamic finance.Keywords: Islamic finance; Covid-19; economic growth.